The influence of fly ash and foam contents on the properties of lightweight foamed concrete - Ngo Si Huy; Mai Thi Hong (Vietnam Journal of Science, Technology and Engineering, 2022)
Due to rapid industrialization and modernization, a large number of both fly ash (FA) and ground granulated blast furnace slag (GGBFS), both by-products from thermal power plants and steel factories, are increasing day by day. Thus, recycling these industrial wastes to produce lightweight foamed concrete (LFC) was investigated in this study. Eight LFC mixtures were designed with different FA content and foam content to investigate their effect on the properties of LFC. Test results indicate that both FA and foam contents had a significant influence on the properties of LFC. The quality of LFC decreased with increasing foam content while the presence of FA improved its properties. The properties of LFC and its dry unit weight had a close relationship, and the correlation between them was described by linear regression. For example, high foam content resulted in more void volumes inside the LFC thus reducing its properties. Meanwhile, the presence of FA minimized the void volume and enhanced the LFC’s properties. All LFCs in this investigation showed good quality, which were classified as grade M3.5-12.5 based on TCVN 9029:2017, which means they can be used as unburnt bricks with significantly low unit weight and thermal conductivity.